A linkage study between HLA and cutaneous malignant melanoma or precursor lesions or both. Issue 6 (December 1984) - Demenais, F; Cesarini, J P; Daveau, M; Cavelier, B; Gony, J; Feingold, N; Hors, J
Abstract : In seven pedigrees displaying the familial atypical multiple mole-melanoma (FAMMM) syndrome, three successive linkage analyses were performed between HLA and an assumed dominant gene determining respectively each of the following affected phenotypes: (1) precursor lesions, (2) cutaneous malignant melanoma (CMM), and (3) precursor lesions or CMM or both. Close linkage could be excluded in (1) and (3). However, if the transmission of malignant melanoma itself were assumed to be due to a single gene different from the one responsible for precursor lesions, a maximum lod score of 1.64 was observed at a recombination fraction of 5%, assuming low penetrance values. These different results are discussed in respect to the possible mechanisms causing the familial distribution of these traits. Two alternative hypotheses were proposed. Either the FAMMM syndrome is a rare genetic entity not closely linked to HLA or the association and transmission of precursor lesions and CMM in families are due to several factors among which HLA might play a role.